2015
DOI: 10.1128/mcb.00365-15
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Internal Ribosome Entry Site-Mediated p53 Translation in Cancer Cells with Defective p53 Response to DNA Damage

Abstract: Synthesis of the p53 tumor suppressor and its subsequent activation following DNA damage are critical for its protection against tumorigenesis. We previously discovered an internal ribosome entry site (IRES) at the 5= untranslated region of the p53 mRNA. However, the connection between IRES-mediated p53 translation and p53's tumor suppressive function is unknown. In this study, we identified two p53 IRES trans-acting factors, translational control protein 80 (TCP80), and RNA helicase A (RHA), which positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 56 publications
(82 reference statements)
0
43
0
Order By: Relevance
“…In a recent study, a novel mechanism of TP53 inactivation in cancer cells was discovered. The study found that in various cancer cell lines, the IRES‐dependent translation of TP53 was inhibited due to reduced levels of ITAFs RHA and TCP80 .…”
Section: Translation Dysregulation In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, a novel mechanism of TP53 inactivation in cancer cells was discovered. The study found that in various cancer cell lines, the IRES‐dependent translation of TP53 was inhibited due to reduced levels of ITAFs RHA and TCP80 .…”
Section: Translation Dysregulation In Cancermentioning
confidence: 99%
“…In a recent study, a novel mechanism of TP53 inactivation in cancer cells was discovered. The study found that in various cancer cell lines, the IRES-dependent translation of TP53 was inhibited due to reduced levels of ITAFs RHA and TCP80 [230]. XIAP: One oncogene that is extensively studied for its tumor initiating properties is XIAP (X-linked inhibitor of apoptosis protein), a protein that inhibits apoptosis.…”
Section: Ires-mediated Translation and Cancermentioning
confidence: 99%
“…This stimulation is significantly enhanced upon exposure to DNA damage as a result of increased binding of TCP80 to the p53 IRES and improved interaction between DHX9 and TCP80. It is predicted that DHX9 likely helps unwind the p53 5′IRES, thereby promoting efficient translation [157, 158]. …”
Section: Biological Functions Of Dhx9mentioning
confidence: 99%
“…Specifically, the breast cancer cell lines, ZR75-1 and MDA-MB-175, which express wild-type p53 but do not exhibit p53 induction following DNA damage, contain extremely low levels of both DHX9 and TCP80 compared to MCF-7 cells (which show a normal p53 response), and exhibit low p53-IRES activity when exposed to DNA damaging agents. IRES-mediated p53 translation was rescued by overexpression of DHX9 and TCP80 [158]. This shows that DHX9 levels can have a direct effect on the ability of p53 to suppress tumourigenesis.…”
Section: Implications Of Dhx9 In Cancer and Its Treatmentmentioning
confidence: 99%
“…An internal ribosome entry site (IRES) is an RNA element that allows for translation initiation (Lampe et al, 2018). Deregulation of IRES-mediated p53 translation promoted the defective p53 response against DNA damage in human cancer cells (Halaby et al, 2015). ER stress, serum deprivation, and hypoxia-induced human acetyl-CoA carboxylase 1 (hACC1) are controlled by IRES sequences (Damiano et al, 2018).…”
Section: Discussionmentioning
confidence: 99%